2012
DOI: 10.1016/j.nimb.2012.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Properties of fast carbon cluster microbeams produced with a tapered capillary

Abstract: a b s t r a c tWe study the transmission properties of fast cluster ions (C n + (n = 2-4) with velocities ranging from 0.89 to 1.79 a.u.) through a single tapered capillary with an outlet diameter of 13.7 lm. We investigate the projectile-velocity dependence of the transmission fraction from the measurements of transmitted particle energy spectra. It is found that the non-fragmentation fraction of C 2 + projectiles increases with decreasing velocity, indicating that fragmentation occurs mainly via close collis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…To describe the observed effect, the authors of work [5] introduced the term "guiding" and explained the guiding effect is due to the deposited charge from the ion impact on the insulating surfaces which prohibit the following ions from close collisions with the capillary walls. The guiding effect was also observed for other types of ions with different energies [6]- [8]. So far, the guiding scenario for the positive ions are widely accepted and clear.…”
Section: Introductionmentioning
confidence: 70%
“…To describe the observed effect, the authors of work [5] introduced the term "guiding" and explained the guiding effect is due to the deposited charge from the ion impact on the insulating surfaces which prohibit the following ions from close collisions with the capillary walls. The guiding effect was also observed for other types of ions with different energies [6]- [8]. So far, the guiding scenario for the positive ions are widely accepted and clear.…”
Section: Introductionmentioning
confidence: 70%
“…The apparatus and experimental procedure are essentially the same as our previous study [8] and only a brief outline is given. Figure 1 shows the experimental setup.…”
Section: Methodsmentioning
confidence: 99%
“…We employed borosilicate glass capillaries with two different outlet diameters of 7.7 and 13.7 μm. The latter capillary was entirely the same as that used in our previous study (details of the capillary characteristics were described in [8]). The taper angle in the exit region was 0.1 • or less.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a realistic value of the enhancement factor may be considered to be less than 2, the work of Nebiki et al demonstrated that a tapered glass capillary can be used as a simple microbeam generator to achieve some beam density enhancement. The capillary microbeam method has since been applied to particle induced x-ray emission (PIXE), RBS (Rutherford backscattering spectrometry), and nuclear reaction analysis with various MeV-energy ions [87][88][89][90][91][92][93][94][95][96][97][98]. The RIKEN group has also started to apply capillary microbeam methods to the irradiation of intracellular organelles [99][100][101].…”
Section: Macro-size Capillariesmentioning
confidence: 99%